Physics and applications of scintillation detectors - Brooks, Francis Dey (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1996)
The papers submitted in this volume present contributions and reviews on the physics of the scintillation process together with contributions to the development of scintillation detection techniques and the use of these techniques in nuclear physics research and in the applications of nuclear methods to other fields.
Keywords: Nuclear physics; Scintillation counters; Nuclear counters; Detectors